Isolasi dan Karakterisasi Jamur Endofit Lamun (Thalassia hemprichii) Dari Kawasan Teluk Tomini - Mahdalena Sy. Pakaya; Wiwit Zuriati Uno; Dewi Rahmawaty Moo; Dizky Ramadani Putri Papeo (State University of Gorontalo, 2022)
Endophytic fungi live in their host tissues. Endophytic fungi can produce compounds similar to their hosts as well. In this case, the use of endophytic fungi can reduce the exploitation of seagrass (Thalassia hemprichii) populations in Tomini Bay. This study aims to isolate and determine the characteristics of the endophytic fungus of seagrass (Thalassia hemprichii) from the Tomini Bay area. The test method used is the isolation and characterization macroscopically and microscopically. The results of the isolation obtained two isolates of endophytic fungi coded J1 and J2 with different characteristics. The isolate code J1 had microscopic characteristics of a yeast-like shape, while the isolate code J2 had the characteristic of non-septate hyphae.